Feasibility and relative validity of a digital photo-based dietary assessment: results from the Nutris-Phone study. Issue 7 (6th March 2018) - Prinz, Nicole; Bohn, Barbara; Kern, Annamarie; Püngel, Deborah; Pollatos, Olga; Holl, Reinhard W
Abstract: Objective: For dietary assessment, mobile devices with a camera can be used as an alternative to hand-written paper records. The Nutritional Tracking Information Smartphone (Nutris-Phone) study aimed to examine relative validity and feasibility of a photo-based dietary record in everyday life. Design: Parallel to the photo-based technique, a weighed record was performed. Participant satisfaction was assessed by questionnaire. A trained nutrition scientist evaluated portion sizes and nutrient content was calculated (DGExpert). Spearman correlation and Bland–Altman analyses were applied. Setting: Healthy, non-pregnant volunteers (≥18 years) without intent to lose weight recruited at Ulm University, Germany. Subjects: Sixty-six participants (36 % males, median age 22·0 (interquartile range 20·0–25·0) years) took pictures of foods and beverages consumed with a commercially available mobile phone. Results: Significant correlation between the photo-based and weighed record was observed: energy ( r =0·991), carbohydrate ( r =0·980), fat ( r =0·972), protein ( r =0·988), fibre ( r =0·941). Bland–Altman analyses indicated comparable means and acceptable 95 % limits of agreement (energy: −345·2 to 302·9 kJ (−82·5 to 72·4 kcal); carbohydrate: −15·2 to 13·1 g; fat: −6·4 to 6·4 g; protein: −5·9 to 5·6 g; fibre: −2·7 to 2·5 g). However, with increasing intake level, underestimation by the digital method was present (except for fat, all P <0·01). Over 80 % of participants were satisfied with the photo-based record. In nearly 90 %, technical implementation was without major problems. Conclusions: Compared with a weighed record, the photo-based dietary record seems to be valid, feasible and user-friendly to estimate energy, macronutrient and fibre intakes, although a systematic bias with increasing levels of intake should be kept in mind.